Analisis faktor resiko kejadian asfiksia neonatorum pada bayi baru lahir Rendah - Dian Eka J (NHM PRESS, 2019)
Fetal life is very dependent on the placentafor oxygen exchange, nutrition and disposal of wasteproducts so that interference with the umbilical andplacental blood flow is almost always cause neonatalasphyxia. According to the data in Space KenangaRoom Sampang Hospital infants with neonatalasphyxia in 2013 as many as 491, and in 2014 in thelast 3 months was found 149 babies. This studyaimed to analyze the risk factors associated with theincidence of neonatal asphyxia in the newborn. Thisstudy is a correlational study, the type of crosssectional study. Were included in the independentvariable, namely maternal age, maternal nutritionalstatus, and maternal age and the dependent variableis the incidence of neonatal asphyxia. The studypopulation of 90 respondents. The sampling methodwith accidentil sampling technique involving 42respondents. Data were analyzed using univariateand bivariate. Results of statistical analysis of testdata using Spearman's Rho with α = 0.05 (ρ <α)between maternal age and asphyxia obtained mostlymaternal age <20 years (79%) with the value ρ =0.006, so there is the effect of maternal age onasphyxia. Between maternal nutrition with asphyxiakejadia obtained the majority of women, includingthe status of malnutrition (95%) with the value ρ =0.041, so that there is the influence of the nutritionalstatus of the mother against asphyxia. Betweengestational age and asphyxia obtained most ofgestational age less (83%) with the value ρ = 0.001,there is the influence of maternal age on theincidence of asphyxia.Furthermore, the authors hopeto all health workers to be more active motivatepregnant women to diligently perform the ANC sothat high-risk pregnancy can be detected early..